60.5k views
0 votes
Please help meee ;_;

Please help meee ;_;-example-1
User Vincy
by
5.1k points

2 Answers

6 votes

Check the picture below.

to get the equation of any straight line, we simply need any two points off of it, so let's use those two from the picture.


(\stackrel{x_1}{-3}~,~\stackrel{y_1}{-6})\qquad (\stackrel{x_2}{2}~,~\stackrel{y_2}{9}) \\\\\\ \stackrel{slope}{m}\implies \cfrac{\stackrel{rise} {\stackrel{y_2}{9}-\stackrel{y1}{(-6)}}}{\underset{run} {\underset{x_2}{2}-\underset{x_1}{(-3)}}} \implies \cfrac{9 +6}{2 +3} \implies \cfrac{ 15 }{ 5 }\implies 3


\begin{array}ll \cline{1-1} \textit{point-slope form}\\ \cline{1-1} \\ y-y_1=m(x-x_1) \\\\ \cline{1-1} \end{array}\implies y-\stackrel{y_1}{(-6)}=\stackrel{m}{3}(x-\stackrel{x_1}{(-3)}) \\\\\\ y+6=3(x+3)\implies y+6=3x+9\implies y=3x+3

Please help meee ;_;-example-1
User Heedfull
by
4.6k points
6 votes

Answer:

Explanation:

(-1, 0) (0,3)

(3-0)/(0+1)

3/1 = 3

y - 0 = 3(x + 1)

y = 3x + 3

User Israr
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.